Congestion Avoidance in Wireless Mesh Networks Based On Multicast Routing Protocols - Al-Jendary, Mohammed A; Al-Sanabani, Maher A (International Journal of Computer Sciences and Engineering, 2025)
Congestion is a major challenge in Wireless Mesh Networks (WMNs) that rely on high mobility, dynamic topology, and limited resources. Congestion is the instability of the network due to unmanaged traffic resulted in exceeding the capacity of the network’s resources which leads to bottleneck stage that can occur at any intermediate node. Therefore, the performance of the network is deteriorating in packet drops, high delays, and low throughput. Therefore, an extensive research has been done for searching an effective algorithm for congestion problem in WMNs. Hence, the demand for effective management of the resources is immensely needed to enhance the network performance with multicast processes that lead to more congestion in the networks due to the high demands of resources in WMNs. Hence, a new scheme has been proposed in this paper to avoid the congestion in WMNs using the concept of target rate that is applied in the MAC layer and based on (MAODV) Multicast Ad-hoc on Demand Distance Vector routing protocol. The simulation results through NS2.26 simulator show the performance of the proposed scheme outperforms the original scheme. Thus, proving a fair distribution of resources among nodes is maintained due to resolving the congestion problem which leads to increases packet delivery ratio and the throughput and reduces the delay thereby increasing the network performance on the whole which is suitable for the emerging applications in WMNs